Delayed Laparoscopic Cholecystectomy After Percutaneous Transhepatic Gallbladder Drainage Versus Emergency Laparoscopic Cholecystectomy for Acute Cholecystitis: A Meta-Analysis - Shengbin Cai; Xianhua Ma (Turkish Journal of Gastroenterology, 2021)
Background: The purpose of this meta-analysis is to appraise the efficacy and safety of delayed laparoscopic cholecystectomy after percutaneous transhepatic gallbladder drainage (PTGBD) versus emergency laparoscopic cholecystectomy (ELC) for acute cholecystitis. Methods: The kinds of literature were searched by Web of Science, PubMed, OVID, Cochrane Library, and EMBASE between the year 2000 and 2019. RevMan 5.3 was used for meta-analysis. Results: Seventeen studies with 2135 participants were included in our study. Compared with the ELC group, delayed laparoscopic cholecystectomy after percutaneous transhepatic gallbladder drainage group (PTGBD group) had a significant better effect in intraoperative bleeding (P = .002), conversion rate to open surgery (P = .02), postoperative complications (P ＜ .00001), bile leakage (P = .01), bile duct injury (P = .02), and wound infection (P = .02). There was no significant difference between the two groups in operative time (P= 32), postoperative hospital stay (P = .30), and intraperitoneal hemorrhage (P = .39). PTGBD group had a significantly longer overall hospital stay than the ELC group (P ＜ .00001). Conclusion: Compared with the ELC group, the PTGBD group has several advantages, including bile duct injury, intraoperative bleeding, bile leakage, conversion rate to open surgery, postoperative complications, and wound infection. The only drawback in the PTGBD group is to lengthen the total hospital stay Cite this article as: Cai S, Ma X. Delayed laparoscopic cholecystectomy after percutaneous transhepatic gallbladder drainage versus emergency laparoscopic cholecystectomy for acute cholecystitis: A meta-analysis. Turk J Gastroenterol. 2021;32(11):945-955.